O aquecimento global entre jornalistas e cientistas : análise retórica do jornalismo científico - Zermiani, Raul Tavela (2010)
In this dissertation we present the analyses about how the Environment newspaper of Folha de S. Paulo shows, in rhetorical terms, manage the subject Global Warming. Our objective was to examine the meaning produced by the use of rhetoric figures, as the metaphor, for example. The methodological proceeding were: a) selection of texts from the first semester of 2008about global warming; b) reading and selection of the texts content the categories of arguments and kinds of rhetorical figures; c) rhetorical examination of selected texts. In order to make the analyses functional of the argument category and rhetorical figures we use the studies of Perelman (1999), Reboul (1998) and Breton (2003). As results we achieve: a) the rhetorical figures are usual into the analyzed texts; b) the metaphor appear as the main figure; c) sometimes figures are not clearly presented to the auditory; d) the arguments makes habitual assumption about the subject, making it been interpreted in a certain way; e) the construction of rhetorical sense is initialized in the selection of arguments to be used by the orator; f) the technical composition of journalistic texts generates the necessity of the use of rhetorical figures (as in the case of composing the lead); g) the betake of rhetorical figures is inevitable in all kind of texts, including journalistic.